Using multidimensional scaling in model choice for congenital oesophageal atresia: similarity analysis of human autopsy organ weights with those from a comparative assessment of Aachen Minipig and Pietrain piglets. (December 2020) - Baumgart, Jan; Deigendesch, Nikolaus; Lindner, Andreas; Muensterer, Oliver J.; Schröder, Arne; Heimann, Axel; Oetzmann von Sochaczewski, Christina
Swine models had been popular in paediatric oesophageal surgery in the past. Although being largely replaced by rodent models, swine experienced a revival with the establishment of minipig models. However, none of them has ever been investigated for similarity to humans. We conducted a pilot study to determine whether three-week old Pietrain piglets and three-month old Aachen Minipigs are suitable for experimental paediatric oesophageal atresia surgery. We tested the operation's feasibility, performed a necropsy, weighed organs, measured organ length and calculated relative weights and lengths, and measured laboratory parameters. We used multidimensional scaling to assess the similarity of the swine breeds with previously published human data. Pietrain piglets had a higher a priori bodyweight than Aachen Minipigs (Δ = 1.31 kg, 95% confidence interval (CI): 0.37–2.23, p  = 0.015), while snout-to-tail length was similar. Pietrain piglets had higher absolute and relative oesophageal lengths (Δ = 5.43 cm, 95% CI: 2.2–8.6; p  = 0.0062, q 1 *  = 0.0083 and Δ = 11.4%, 95% CI: 5.1–17.6; p  = 0.0025, q 3 *  = 0.0053). Likewise, absolute and relative small intestinal lengths were higher in Pietrains, but all other parameters did not differ, with the exception of minor differences in laboratory parameters. Multidimensional scaling revealed three-week old Pietrain piglets to be similar to two-month old humans based on their thoracoabdominal organ weights. This result indicates three-week old Pietrain piglets are a suitable model of paediatric oesophageal atresia surgery, because clinically many procedures are performed at around eight weeks age. Three-month old Aachen Minipigs were more dissimilar to eight-week old humans than three-week old Pietrain piglets.